Arabic Grammar Application in Malay l Tatbiq Qawa’id al-Lugah al-‘Arabiyyah fi al-Lugah al-Malayuwiyyah - Dewi, Eva; Munthe, Bermawy; Afandi, Zamzam (Universitas Islam Negeri Raden Intan Lampung, 2021)
Bustan al-Katibin is one of the first famous book written by Raja Ali Haji in 1850 AD. It is used in tradisional school in the Riau Islands, Johor and Singapore. This research was significant to be done because Raja Ali Haji had explained that language is not only in linguistic studies, but also in the aspects of ontology, epistemology and cosmology. This study aimed to examine the application of Arabic grammar using Malay by comparing the Arabic grammar system and the Malay language system that has been used in this book. This research was a critical study with content analysis techniques. The primary data source was the Bustan al-Katibin book. Meanwhile, the secondary data sources were books and articles related to this study. The result of this research was the learning of Arabic grammar in Malay as presented in Bustan al-Katibin about aspects of language consisting of: isim, fi'il, and huruf, as a way to help understanding the Arabic grammar. Although the explanation and structure are less systematic in this book, the advantages of this book cannot be ignored because it does not only contain the knowledge of language, but even understanding of language in the system of cosmology, ontology, and epistemology. UU Hamidy explained that his work had been used as a reference in teaching in the nineteenth and early twentieth centuries in schools in the Riau Islands, Johor, and Singapore. Teeuw asserted that this work was a part of Arabic language study.